The capitalist spirit and endogenous growth - Ronald Ravinesh Kumar; Peter Stauvermann; Frank Wernitz (Journal of Risk and Financial Management, 2022)
The aim of the study is to investigate the influence of the capitalist spirit in conjunction with the distribution of income on economic growth. The capitalist spirit is represented by the fact that savings rates increase with increasing relative income. We extend an endogenous AK growth model in an overlapping generational framework by implementing imperfect competition and Cournot competition. Using this model, we investigate the influence of profits on the intra- and inter-generational distributions of income and economic growth. While increasing incomes lead to a more unequal intra-generational distribution and to a redistribution of income from the old to the young generation, the impact on economic growth is in general ambiguous, although under specific assumptions it becomes positive. Furthermore, the model shows that increasing market power of firms is associated with declining labor and capital shares, declining interest rates, and an increased wealth-to-income ratio.
Keywords: 330; oligopolistic competition; endogenous growth; spirit of capitalism; savings rate; price market power; distribution of income